Radiographic measure of aorta calcification is a site‐specific predictor of bone loss and fracture risk at the hip - BAGGER, Y. Z.; TANKÓ, L. B.; ALEXANDERSEN, P.; QIN, G.; CHRISTIANSEN, C. (Journal of internal medicine, 2006)
. Objective.  To investigate whether aorta calcification (AC) – a surrogate marker of atherosclerosis – is an independent indicator of low bone mass density (BMD), accelerated bone loss, and risk of future fractures in postmenopausal women. Design.  A prospective epidemiological study. Follow‐up period was 7.5 years. Setting.  Community‐based sample followed by a research institute. Subjects.  A total of 2662 generally healthy postmenopausal women with a mean age of 65.0 ± 7.1 years at baseline. Main outcome measures.  Annual rate of changes in BMD (DEXA) and AC (X‐rays), vertebral fractures (X‐rays), hip fractures (questionnaire). Results.  Advanced AC at baseline was significantly associated with lower BMD and accelerated bone loss from the proximal femur. In a multivariate logistic regression model, age (OR 1.1, 95% CI 1.0–1.2, P = 0.02), body mass index (BMI; OR 0.9, 95% CI 0.8–1.0, P = 0.03) and the severity of AC (OR 2.3, 95% CI 1.1–4.8, P = 0.03) were independent predictors of hip fractures. Adjusted OR for vertebral fracture was 1.2 (95% CI 1.0–1.5, P = 0.12). Conclusions.  Aorta calcification seems to independently contribute to the development of osteoporosis in the proximal femur. Further studies are needed to clarify whether effective atherosclerosis prevention lowers hip fracture risk.